PENJATUHAN PIDANA NIHIL DALAM TINDAK PIDANA KORUPSI DAN PENCUCIAN UANG - I Made Gede Kariana (Lex LATA, 2024)
In the practice of decision, the judge's consideration in imposing a zero sentence on corruption and money laundering cases according to the Corruption Court Decision at the Central Jakarta District Court Number 50/Pid.Sus-TPK/2021/PN.Jkt.Pst, is because the defendant had previously been sentenced to life imprisonment in another separate but similar case. The next main consideration is because the prosecution for death penalty by the Public Prosecutor cannot be considered by the Judge because it is not in accordance with the Public Prosecutor's Indictment. The criminal law policy in setting the imposition of zero sentences in the future, is the arrangement of concurrent criminal acts and their punishment system according to the provisions of Article 65 of the Criminal Code in the National Criminal Code including Article 67 of the Criminal Code regarding zero crimes which is currently confirmed by legal certainty in Article 131 of Law Number 1 of 2023 concerning the Criminal Code even though it has not yet been promulgated.